Representasi Relasi Sehat dan Pemulihan Diri Pada Lirik Lagu “AH” Karya Nadin Amizah - Mufti Fauzi; Santi Puspita Sari; Alfi Fauzia Hakim (Jurnal Inovasi Komunikasi, 2026)
This study examines the representation of healthy relationships and self-healing in the song Ah by Nadin Amizah using Charles Sanders Peirce’s semiotic framework. In recent years, popular music has increasingly functioned not only as entertainment but also as a cultural text that shapes public understanding of emotional well-being and relational meanings. However, limited studies have specifically explored how song lyrics construct relationships as psychological safe spaces and media for self-recovery. This research aims to identify and interpret the system of signs within the lyrics of Ah that represent healthy relationships and self-healing processes. This study employs a qualitative method with a communication semiotics approach. The data consist of lyrical texts analyzed through Peirce’s triadic model of sign, object, and interpretant. Data were collected through documentation and literature study and examined using close reading techniques to capture symbolic, affective, and relational meanings. The findings reveal that the lyrics of Ah construct relationships as non-exploitative emotional spaces, emphasizing mutual effort, emotional openness, spiritual gratitude, and future-oriented hope. The song represents relationships not as sources of emotional conflict but as spaces of psychological security, identity recovery, and emotional sustainability. This study contributes to communication studies by positioning song lyrics as cultural texts that actively construct meanings of healthy relationships and emotional well-being in popular culture.